2016
DOI: 10.1007/s11356-016-6772-4
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxic effects of cadmium in human head and neck cell line SQ20B

Abstract: As cadmium may be involved in the etiology of head and neck cancers, we investigated in the present work, the cytotoxic and genotoxic effects of Cd on human larynx cells. SQ20B cells were exposed to 25 and 50 μM Cd for 48 and 72 h. Results showed a dose-dependent decrease in cell viability, especially after 48 h, associated with mitochondria alterations as showed by transmission electronic microscopy. Surprisingly, the flow cytometry shows that the cells treated with Cd have a normal proliferative cycle like t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 61 publications
1
3
0
Order By: Relevance
“…A study conducted by Sa et al (73)., investigated the association between heavy metal exposure and cancer in renal cells. Using both SEM, Transmission Electron Microscopy (TEM) and X-Ray microanalysis, the results obtained indicated that with increased levels of Cr, increased changes in cellular morphology was observed (73).Similar results were shown by Trabelisi et al (74).,…”
Section: + Crsupporting
confidence: 81%
“…A study conducted by Sa et al (73)., investigated the association between heavy metal exposure and cancer in renal cells. Using both SEM, Transmission Electron Microscopy (TEM) and X-Ray microanalysis, the results obtained indicated that with increased levels of Cr, increased changes in cellular morphology was observed (73).Similar results were shown by Trabelisi et al (74).,…”
Section: + Crsupporting
confidence: 81%
“…Moreover, to address the potential Cd-related toxicity of the QDs, control experiments with CdCl 2 were also performed, which has been classified as a group 1 carcinogen and is known to show positive results in common mammalian in vitro genotoxicity assays. [53][54][55] As a preliminary test for the desired automated genotoxicity test with our automated microscopy platform, spectroscopic measurements (absorption spectra; for the luminescent QDs also emission spectra) of the NPs were carried out to assess potential interferences with the fluorescent reporters DAPI and AF488 used in γ-H2AX assay. The 30 nm Au-NPs showed a plasmonic absorption band at around 525 nm, whereas the FeO x -NPs displayed an unstructured absorption spectrum with an onset of absorption at around 600 nm and an increasing absorbance towards the ultraviolet region (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…CdCl 2 was chosen as the positive control because it is a potent inducer of γ-H2AX foci. 53 Chemical fixation of the HEp-2 cells was performed with PBS-buffered 2% formaldehyde solution for 15 min at RT. After three washing steps with PBS the cells were incubated for 5 min with 0.1% Triton X-100 in PBS at 4°C, followed by three more washing steps with PBS + 0.5% BSA to block unspecific binding.…”
Section: Np Toxicity Testingmentioning
confidence: 99%
See 1 more Smart Citation